Effect of compaction and soil moisture on the effective permeability of sands for use in methane oxidation systems. (15th April 2020) - van Verseveld, Charlotte J.W.; Gebert, Julia
Highlights: For the researched soils, compaction influences permeability more than moisture. Compaction mainly influences the coarse pores which contribute most to permeability. The relationship between air-filled porosity and permeability is soil-specific. Moisture can induce inter-aggregate macroporosity and thereby increase permeability. Abstract: Effective gas permeability is an important parameter in the design of methane oxidation systems, governing diffusive oxygen ingress and the spatial spread of landfill gas. The influences of soil texture, compaction, soil moisture and the resulting air filled porosity on the gas permeability were researched by performing pressure loss experiments on two loamy sands, currently in use as methane oxidation layer material. These experiments mimicked the influence of the intrinsic soil properties, the construction method (compaction) and the local climate (soil moisture) on the soils' permeability. In both soils, effective and specific permeability were strongly impacted by the level of soil compaction, whereas increasing moisture contents had little effect in one of the soils, only reducing effective permeability when a certain threshold was exceeded. In the other soil, structure-forming processes induced by the addition of water led to an increase in both effective and specific permeability with increasing moisture. It is concluded that the spatial spread of the landfill gas in the gas distribution layer is predominantly affected by texture and compaction of the overlying methane oxidation layer. In terms of methane oxidation system design, the choice of material and construction method have more impact on gas permeability than seasonal changes in soil moisture in moderate climates. Furthermore, air filled porosity on its own is not adequate to estimate the effective permeability of loamy sand for methane oxidation layers. Further research should address the estimation of effective gas permeability based upon soil texture, bulk density and soil moisture combined.